If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -16) + -1(x + 10) = -22 Reorder the terms: 3(-16 + x) + -1(x + 10) = -22 (-16 * 3 + x * 3) + -1(x + 10) = -22 (-48 + 3x) + -1(x + 10) = -22 Reorder the terms: -48 + 3x + -1(10 + x) = -22 -48 + 3x + (10 * -1 + x * -1) = -22 -48 + 3x + (-10 + -1x) = -22 Reorder the terms: -48 + -10 + 3x + -1x = -22 Combine like terms: -48 + -10 = -58 -58 + 3x + -1x = -22 Combine like terms: 3x + -1x = 2x -58 + 2x = -22 Solving -58 + 2x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '58' to each side of the equation. -58 + 58 + 2x = -22 + 58 Combine like terms: -58 + 58 = 0 0 + 2x = -22 + 58 2x = -22 + 58 Combine like terms: -22 + 58 = 36 2x = 36 Divide each side by '2'. x = 18 Simplifying x = 18
| 75+10.5x=15.50x | | -4(3y-8)+3(2y+10)= | | 0.6(x-8)=3.6 | | N×3/5=1 | | 14n+11=5(n+4) | | 5(x-3)-4(2x-1)=100 | | 6(x+1)-7x=-14 | | 3/8-n=2/24 | | 7(r-7)= | | 4y-z=0 | | x(5x-2)-19(5x-2)=0 | | 2(4n+8)+7n-2n=178 | | 5m+20=8m-16 | | 9(3+v)= | | 9h-2h+-18h=14 | | 2x+9y+5x-2=10 | | 6x-4z=0 | | 4x+3(x+1)=1 | | 5/2x=53 | | 2x^2-4x-y^2-24y-13=0 | | 7(-1+4x)-2=47 | | 3(h+1)=15 | | -8(8-2m)=8(m-2) | | 1250=(.1)*x(300-x) | | 9-9a=5-(-3a) | | 5x^2-97x-38=0 | | 7(x-7)=0 | | -15n+18n+4n-20n=13 | | 1250=2x(300-x) | | 1/3x-4=8 | | 6x+16-5x=-3-10 | | g(-4t)=t-4 |